The 2017 May 20 stellar occultation by the elongated centaur (95626) 2002 GZ32. Issue 4 (31st December 2020) - Santos-Sanz, P; Ortiz, J L; Sicardy, B; Benedetti-Rossi, G; Morales, N; Fernández-Valenzuela, E; Duffard, R; Iglesias-Marzoa, R; Lamadrid, J L; Maícas, N; Pérez, L; Gazeas, K; et al.
ABSTRACT: We predicted a stellar occultation of the bright star Gaia DR1 4332852996360346368 (UCAC4 385-75921) ( mV = 14.0 mag) by the centaur 2002 GZ32 for 2017 May 20. Our latest shadow path prediction was favourable to a large region in Europe. Observations were arranged in a broad region inside the nominal shadow path. Series of images were obtained with 29 telescopes throughout Europe and from six of them (five in Spain and one in Greece) we detected the occultation. This is the fourth centaur, besides Chariklo, Chiron, and Bienor, for which a multichord stellar occultation is reported. By means of an elliptical fit to the occultation chords, we obtained the limb of 2002 GZ32 during the occultation, resulting in an ellipse with axes of 305 ± 17 km × 146 ± 8 km. From this limb, thanks to a rotational light curve obtained shortly after the occultation, we derived the geometric albedo of 2002 GZ32 ( pV = 0.043 ± 0.007) and a 3D ellipsoidal shape with axes 366 km × 306 km × 120 km. This shape is not fully consistent with a homogeneous body in hydrostatic equilibrium for the known rotation period of 2002 GZ32 . The size (albedo) obtained from the occultation is respectively smaller (greater) than that derived from the radiometric technique but compatible within error bars. No rings or debris around 2002 GZ32 were detected from the occultation, but narrow and thin rings cannot be discarded.